Bibliometric Analysis of Intelligence and Espionage Activities in Indonesia - Syahputra, Alfin Reza (BRILIANT: Jurnal Riset dan Konseptual, 2024)
This research examines various strategic intelligence research over the last 10 years. This research adopts a qualitative method based on the results of a bibliometric analysis review of various literature. The literature is obtained from Google Scholar with the help of the Publish or Perish program. The literature search was limited to the year 2015 to 2023 with selected keywords and titles, including the keywords "intelligence", "intelligence agent", and "strategic intelligence". The selection of literature through meta-data analysis using the PRISMA and 94 selected pieces of literature were obtained and analyzed with the help of the VOSviewer program. The literature review results show that studies on intelligence over the last 10 years have carried out a lot of research on intelligence and radicalism. The final finding is that intelligence-related research can be grouped into 6 groups, namely in the fields of security, immigration and elections, prosecutors, terrorism, intelligence, and radicalism.